Effect of Quality of Work Life on Performance Employees with Variables Work Commitments Intervening in Millenial Generation Employees in PT Pelabuhan Indonesia II (Persero) Head Office - Fella Fatchiya; I Ketut R. Sudiarditha; Henry Eryanto (Program Studi S3 Ilmu Manajemen, 2021)
Abstract: This study aims to analyze the influence of quality of work life on employee performance with work commitment as an intervening variable on employees of the millennial generation of PT head office. Port of Indonesia II (Persero). Determination of samples using Probability Sampling method with 160 respondents and analyzed using Structural Equation Model Partial Least Square (SEM PLS) analysis method. The results of the study showed that 1) the quality of work life has a positive and significant effect on employee performance, indicating that if the quality of work life in employees of the millennial generation of PT Pelabuhan Indonesia II (Persero) the better the employee performance will increase, 2) the quality of work life will have a positive and significant effect on work commitment, indicating that if the Quality of Work Life in employees of the millennial generation of PT Pelabuhan Indonesia II (Persero) the better then the employee's work commitment will increase , 3) work commitments have a positive and significant effect on employee performance, indicating that if the Work Commitment to millennial employees of PT Pelabuhan Indonesia II (Persero) is getting better then the Employee Performance will increase, and 4) the quality of work life on employee performance through work commitment has a positive and significant influence, showing an increase in the Work Commitment of millennial employees of PT Pelabuhan Indonesia II (Persero) able to mediate the influence of Quality of Work Life on Employee Performance.